Monitoring and forecasting the condition of structures in the small river basins in southern Russia - Ivankova, Tatyana V.; Fesenko, Lev N. (Vestnik MGSU, 2023)
Introduction. The southern regions of Russia need to adapt to higher peak river flows and flash floods. Since 1960, the number of recorded flood events has increased. The intensity and severity of flood events tend to decrease, but their annual frequency is increasing. This illustrates the social component of flooding. Trends in the number of flood events are closely related to the increasing population in river valleys. “Integrated management” of construction sites in river basins is based on three elements: monitoring, forecasting and early warning, vulnerability assessment, mitigation and response. The purpose of this study is to establish means of prediction, risk assessment of operational construction projects in river basins taking into account the current natural and climatic factors. Materials and methods. The research is based on the factual material collected in the field studies in the river basins of recreational regions of southern Russia. Design, construction and operational documentation of complex structures was analyzed and their structural elements were evaluated. Results. On the basis of the carried out theoretical, field and numerical researches, the problem of increasing ecological safety of the urban environment was solved by monitoring, assessing, ranging of the technical condition of building structures and forecasting risks in the urbanized areas of river basins. The results of the research should be considered as a basis of practical methods for the complex estimation of ecological safety of natural and technical system of river basins. Further development of the topic can be connected with the scaling studies of urbanized territories, monitoring crisis sites and forecasting of the further condition of construction projects by subjects. Conclusions. The developed software package has practical importance, the product is implemented in the Republic of Crimea, in the operation of the long-term operated HES complexes of the Partizanskoe reservoir supplying water to the city of federal importance Simferopol and the Alminsky reservoir irrigating Bakhchisaray region of the peninsula and it is also being tested in the Krasnodar Territory, the Republic of Dagestan, the Stavropol Territory and Caucasian Mineral Waters.